2012
DOI: 10.1007/s13337-012-0111-2
|View full text |Cite
|
Sign up to set email alerts
|

VP292 of White spot syndrome virus Interacts with VP26

Abstract: Interactions between virus structural proteins are suggested to be crucial for virus assembly. Many steps in the process of white spot syndrome virus (WSSV) assembly and maturation remain unclear. In this paper, we discovered a new interaction of WSSV VP292. Temporaltranscription analysis showed that VP292 is expressed in the late stage of WSSV infection. Western blot and matrixassisted laser desorption ionization MS assays showed that VP292 interacts with VP26, a major envelope protein. Farwestern blot provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…This might explain the difference in the binding activities of the two AKs. VP26 was previously identified as an integral linker protein and can bind to host effector proteins to help transport virions into host cells (30,33,34). Previous studies found that viruses use host cell kinases for their replication, and arginine kinase has multiple functions in WSSV infection (21,35).…”
Section: Discussionmentioning
confidence: 99%
“…This might explain the difference in the binding activities of the two AKs. VP26 was previously identified as an integral linker protein and can bind to host effector proteins to help transport virions into host cells (30,33,34). Previous studies found that viruses use host cell kinases for their replication, and arginine kinase has multiple functions in WSSV infection (21,35).…”
Section: Discussionmentioning
confidence: 99%
“…The VP41A envelope protein is known to interact with VP26, VP56 and VP28 envelope proteins [40,44] and with the viral envelope protein VP51A (VP52A for AF332093) [45]. It has been suggested that VP26 is anchored to the envelope with its N-terminal hydrophobic region, as a C-terminal region binds to the nucleocapsid [46], while VP51A is a type II transmembrane protein, with a transmembrane domain highly hydrophobic at its N-terminus and an exposed C-terminus on the virion surface [47].…”
Section: Discussionmentioning
confidence: 99%
“…The correct rLvRPL7 was expressed in E. coli Top10. The rLvRPL7 was confirmed by MS analysis and purified by affinity chromotography using a column of TALON Metal Affinity Resin as previously described [21].…”
Section: Recombinant Expression Of Lvrpl7 In Escherichia Colimentioning
confidence: 99%